2022
DOI: 10.1371/journal.pmed.1003994
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of chikungunya virus infections among Kenyan children with neurological disease, 2014–2018: A cohort study

Abstract: Background Neurological complications due to chikungunya virus (CHIKV) infection have been described in different parts of the world, with children being disproportionately affected. However, the burden of CHIKV-associated neurological disease in Africa is currently unknown and given the lack of diagnostic facilities in routine care it is possible that CHIKV is an unrecognized etiology among children with encephalitis or other neurological illness. Methods and findings We estimated the incidence of CHIKV inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Thus, without laboratory testing, passive clinical reporting of DENV infection is not a reliable means for public health surveillance for this re-emerging infection. A similar study to ours uncovered a large burden of chikungunya virus infection among Kenyan children [ 29 ]. The high prevalence and force of infection of malaria, in combination with lack of routine surveillance for arboviruses such as DENV or chikungunya virus, contribute towards under-recognition of alternate or concomitant causes for AFI and over-diagnosis of malaria [ 30 ].…”
Section: Discussionsupporting
confidence: 72%
“…Thus, without laboratory testing, passive clinical reporting of DENV infection is not a reliable means for public health surveillance for this re-emerging infection. A similar study to ours uncovered a large burden of chikungunya virus infection among Kenyan children [ 29 ]. The high prevalence and force of infection of malaria, in combination with lack of routine surveillance for arboviruses such as DENV or chikungunya virus, contribute towards under-recognition of alternate or concomitant causes for AFI and over-diagnosis of malaria [ 30 ].…”
Section: Discussionsupporting
confidence: 72%
“…We found that school-age stage accounts for a disproportionately large number of cases. The school-age stage has been identified as a demographic group of great significance in contributing to a higher incidence of CHIKV cases, as reported in several studies [21][22][23][24] . These studies have demonstrated a negative correlation between age and the incidence of CHIKV infection, suggesting that the school-age population may be particularly vulnerable to CHIKV.…”
Section: Discussionmentioning
confidence: 91%
“…However, since this mutation was identified in both fatal and survival cases, it is unlikely to be responsible for fatal outcomes. Indeed, CNS infection and fatal CHIK do not appear to be restricted to a particular CHIKV lineage and have been reported in patients from several regions affected by different CHIKV lineages, such as Asian, 15 , 59 ECSA, 11 , 12 , 41 and the Indian Ocean lineage. 60 , 61 Nevertheless, the effects of E2-R242 mutation on CHIKV infection should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 Other complications, such as ophthalmologic, cardiac, and neurological involvement, have also been described in CHIK patients. 1 , 7 , 10 , 11 …”
Section: Introductionmentioning
confidence: 99%